2005
DOI: 10.2337/diabetes.54.suppl_2.s137
|View full text |Cite
|
Sign up to set email alerts
|

Psammomys Obesus, a Model for Environment-Gene Interactions in Type 2 Diabetes

Abstract: Type 2 diabetes is characterized by insulin resistance and progressive ␤-cell failure. Deficient insulin secretion, with increased proportions of insulin precursor molecules, is a common feature of type 2 diabetes; this could result from inappropriate ␤-cell function and/or reduced ␤-cell mass. Most studies using tissues from diabetic patients are retrospective, providing only limited information on the relative contribution of ␤-cell dysfunction versus decreased ␤-cell mass to the "␤-cell failure" of type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 43 publications
(72 reference statements)
1
53
0
3
Order By: Relevance
“…Also in vitro studies have shown a synergistic toxic effect of high glucose and saturated NEFA, a process termed glucolipotoxicity, leading to beta cell dysfunction and death [19,20]. However, most of the in vivo data were obtained in animals such as the Zucker diabetic fatty rat (ZDF) [21], the db/db mouse [22] or the gerbil Psammomys obesus [23], which are obese and hyperlipidaemic, and have extreme hyperglycaemia. Very high glycaemia alone can negatively impact on these processes in the absence of hyperlipidaemia [24,25], so there is a need to better understand the biochemical basis of beta cell failure in milder models of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Also in vitro studies have shown a synergistic toxic effect of high glucose and saturated NEFA, a process termed glucolipotoxicity, leading to beta cell dysfunction and death [19,20]. However, most of the in vivo data were obtained in animals such as the Zucker diabetic fatty rat (ZDF) [21], the db/db mouse [22] or the gerbil Psammomys obesus [23], which are obese and hyperlipidaemic, and have extreme hyperglycaemia. Very high glycaemia alone can negatively impact on these processes in the absence of hyperlipidaemia [24,25], so there is a need to better understand the biochemical basis of beta cell failure in milder models of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…When these animals are transferred from their natural low-energy saltbush diet to more energy-dense rodent laboratory chow, the initial response is an increase in BCM to compensate for the increased insulin demand, followed by development of hyperglycaemia. This animal model is characterised by fast depletion of insulin stores as hyperglycaemia becomes manifest [23,24]. Not all animals become hyperglycaemic as some are resistant to the high-energy diet and stay normoglycaemic (non-responders).…”
Section: Introductionmentioning
confidence: 99%
“…1B). P. obesus has emerged as a model for research into diet-induced type II diabetes because, if provided with high carbohydrate diets, the majority of individuals become obese and develop classic diabetes symptoms, in the most extreme cases leading to pancreatic failure and death (1)(2)(3)(4).…”
mentioning
confidence: 99%